The super predators - Varty, Dave; Schorman, Tedd; Michael, Richard; Masai Mara. Kenya; Londolozi game reserve. South Africa ([U.K] : Creation Entertaiments, 1992)
The super predators was filmed over three years at Londolozi Game Reserve in South Africa and on Kenya's Masai Mara. It captures in particular the breathtaking moments of these super predators hunting. Dramatic slow-motion action replays allow the viewer opportunity of observing all the subtleties of these magnificent hunters in action.
'Filmed on location (at) Masai Mara, Kenya ; Londolozi Game Reserve.
Executive producers, Dave Varty, Tedd Schorman.
Camera, John Varty ; narrator, Michael Richards.
Narrator : Michael Richards.
Keywords: Carnivora -- Africa; Predatory animals -- Africa; Predation (Biology)